Essential Oils Profile and Biological Activities of Zingiber spp - Sabrina Mei Mei, Bong (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The objective of this study was to evaluate and compare the chemical composition of the essential oil from several Zingiber spp. by hydrodistillation method and later identify the chemical composition of the essential oil which was separated into three parts namely the stems, rhizomes and the leaves. Besides, the second objective of this study is to determine the biological activity of essential oils namely the cytotoxicity and antitermite activity of the essential oil. For the identification of chemical composition of the Zingiber, gas chromatography-flame ionization detector (GC-FID) and gas chromatography massspectrometry (GC-MS) were carried out. On the other hand, brine shrimp lethality bioassay and antitermite test were also carried out in order to determine the biological activities respectively. Generally, the rhizome part of the oil contain the highest percentage of essential oil followed by the leaves and the stem. The result obtained from the five Zingiber species revealed that sesquiterpene and monoterpene compound was the predominant compound present in the essential oils in general. The cytotoxicity properties of Zingiber zerumbet (3.00 µL/mL) is the highest followed by Zingiber officinale var. rubra (LC50=4.92 µL/mL), local Zingiber officinale (LC50=5.54 µL/mL) and imported Zingiber officinale (LC50=8.03 µL/mL). The antitermite property was found to have similar trend as the lethality bioassay with Zingiber zerumbet having the lowest LC50 value of 0.30%, followed by Zingiber officinale var. rubra (LC50=0.50%), local Zingiber officinale (LC50=0.55%) and imported Zingiber officinale (LC50=0.80%).